Ordinary generating functions for coefficients of some Dirichlet series

The Dirichlet series a_n corresponding to a power of the Riemann zeta function \zeta(s)^m = \sum\limits_{n=1}^{\infty}\frac{a_n}{n^s} has the ordinary generating function:

\sum \limits_{n=1}^{\infty} a_nx^n = x + {m \choose 1}\sum \limits_{a=2}^{\infty} x^{a} + {m \choose 2}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} + {m \choose 3}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc} + {m \choose 4}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} \sum \limits_{d=2}^{\infty} x^{abcd} +...

Examples:
\sum \limits_{n=1}^{\infty} 1(n)x^n = x + \sum \limits_{a=2}^{\infty} x^{a}

\sum \limits_{n=1}^{\infty} \tau(n)x^n = x + 2\sum \limits_{a=2}^{\infty} x^{a} + \sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab}

\sum \limits_{n=1}^{\infty} \tau_3(n)x^n = x + 3\sum \limits_{a=2}^{\infty} x^{a} + 3\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} + \sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc}

\sum \limits_{n=1}^{\infty} \tau_4(n)x^n = x + 4\sum \limits_{a=2}^{\infty} x^{a} + 6\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} + 4\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc} + \sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} \sum \limits_{d=2}^{\infty} x^{abcd}

\sum \limits_{n=1}^{\infty} \mu(n)x^n = x - \sum \limits_{a=2}^{\infty} x^{a} + \sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} - \sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc} + \sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} \sum \limits_{d=2}^{\infty} x^{abcd} -...

\sum \limits_{n=1}^{\infty} \mu_2(n)x^n = x - 2\sum \limits_{a=2}^{\infty} x^{a} + 3\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} - 4\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc} + 5\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} \sum \limits_{d=2}^{\infty} x^{abcd} -...

\sum \limits_{n=1}^{\infty} \mu_3(n)x^n = x - 3\sum \limits_{a=2}^{\infty} x^{a} + 6\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} - 10\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc} + 15\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} \sum \limits_{d=2}^{\infty} x^{abcd} -...

\sum \limits_{n=1}^{\infty} \mu_{-1/2}(n)x^n = x - \frac{1}{2}\sum \limits_{a=2}^{\infty} x^{a} + \frac{1*3}{2*4}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} - \frac{1*3*5}{2*4*6}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc} +...

\sum \limits_{n=1}^{\infty} \mu_{1/2}(n)x^n = x + \frac{1}{2}\sum \limits_{a=2}^{\infty} x^{a} - \frac{1}{2*4}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} + \frac{1*3}{2*4*6}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc} +...

\sum \limits_{n=1}^{\infty} \mu_{-1/3}(n)x^n = x - \frac{1}{3}\sum \limits_{a=2}^{\infty} x^{a} + \frac{1*4}{3*6}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} - \frac{1*4*7}{3*6*9}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc} +...

\sum \limits_{n=1}^{\infty} \mu_{1/3}(n)x^n = x + \frac{1}{3}\sum \limits_{a=2}^{\infty} x^{a} - \frac{2}{3*6}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} + \frac{2*5}{3*6*9}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc} +...

\sum \limits_{n=1}^{\infty} D(n)x^n = x + \sum \limits_{a=2}^{\infty} x^{a} + \frac{1}{2!}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} x^{ab} + \frac{1}{3!}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} x^{abc} + \frac{1}{4!}\sum \limits_{a=2}^{\infty} \sum \limits_{b=2}^{\infty} \sum \limits_{c=2}^{\infty} \sum \limits_{d=2}^{\infty} x^{abcd} +...

Advertisements
This entry was posted in Uncategorized. Bookmark the permalink.